2011
DOI: 10.1111/j.2042-7158.2011.01438.x
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin inhibited hydrogen peroxide-induced vascular smooth muscle cells proliferation and migration by suppressing the Src and Akt signalling pathways

Abstract: These findings strongly suggested that luteolin suppresses H(2) O(2) -directed migration and proliferation in VSMCs partially due to down-regulation of the Akt and Src signalling pathways, which are important participants in the processes of migration and proliferation of VSMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 32 publications
2
30
0
1
Order By: Relevance
“…Caspase, a family of cysteine proteases, is known to form integral parts of the apoptotic pathway 13) . Therefore, we investigated the protein levels and activities of caspase-3.…”
Section: Effect Of Salidroside On Expression Of Caspase Protease Famimentioning
confidence: 99%
“…Caspase, a family of cysteine proteases, is known to form integral parts of the apoptotic pathway 13) . Therefore, we investigated the protein levels and activities of caspase-3.…”
Section: Effect Of Salidroside On Expression Of Caspase Protease Famimentioning
confidence: 99%
“…It has been reported that H 2 O 2 can activate Axl to facilitate VSMC migration via an Aktdependent pathway [28,29]. In addition, neointima formation in response to cuff injury was reduced in Axl knockout mice compared with Axl wild-type mice [28].…”
Section: Discussionmentioning
confidence: 96%
“…It has been previously reported that H 2 O 2 activates Axl (a redoxsensitive receptor tyrosine kinase) and its downstream Akt pathway to induce VSMC migration and proliferation [28,29]. Here, we blocked Akt with either Akt inhibitor IV that targets the ATP-binding site of a kinase upstream of Akt, or Akt inhibitor X that suppresses the kinase reactivity of Akt by inhibiting its phosphorylation.…”
Section: Trpm2 Mediates Ros-induced Activation Of Axl/akt Pathway In mentioning
confidence: 89%
“…3,4 Assim, a fitoterapia é um método racional e alopático, baseado em evidências científicas, empregado no tratamento médico de váriaspatologias. 5 Um levantamento bibliográfico cobrindo apenas os primeiros meses de 2012 e considerando apenas o mecanismo de ação dos princípios ativos envolvidos, mostra a eficácia das plantas medicinais no tratamento da doença de Alzheimer [6][7][8] , de doenças cardíacas [9][10][11][12] , da malária 13,14 , da leishmania 15 , da esquistossomose 16 , do câncer [17][18][19][20][21][22] , do herpes anti-inflamatório [26][27][28] , como antiúlcera 28,29 ,como antinociceptivo 30 , como antidiabético 31,32 e antidiurético 33 .…”
Section: Introductionunclassified